Penyuluhan Hukum bagi Penerima Bantuan Pangan Non Tunai Berdasarkan Undang-undang Nomor 16 Tahun 2011 tentang Bantuan Hukum: Legal Counseling for Recipients of Non-Cash Food Assistance Based on Law Number 16 of 2011 Concerning Legal Aid - Hidayat, Muhammad Syarif; Saputri, Annisa Nur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Poor people who have problems with the law have the right to receive legal assistance from the beginning of the investigation until there is a court decision that has permanent legal force. Providing legal aid for poor people has been accommodated in Law Number 16 of 2011 concerning legal aid. The aim is to identify problems and efforts that must be made so that providing legal assistance to poor people can be carried out optimally. This research is field research, where all data obtained comes from the field, combined with an empirical juridical research approach. The data collection techniques used in this article are techniques, observation, documentation, and field notes. This outreach activity resulted in the conclusion that this activity was very beneficial for families receiving Non-Cash Food Assistance (BPNT) benefits in Wirosari District, Grobogan Regency. Through this outreach, we also raise public awareness of the existence of free legal assistance as regulated in Law Number 16 of 2011.